Effect of rhizobial inoculants on yield and yield components of faba bean (Vicia fabae L.) on vertisol of Wereillu District, South Wollo, Ethiopia - Samuel Adissie Gedamu; Enyew Adgo Tsegaye; Tesfaye Feyisa Beyene (CABI Agriculture and Bioscience)
Abstract Background Nitrogen fixation by legumes like faba bean is a cheap way of fixing atmospheric nitrogen to plant available form. However, the inoculation of grain legumes with rhizobium bacteria are poorly researched in Amhara Region of Ethiopia. Methods Thus, a study to examine the effects of rhizobium leguminosarum (var vicae) strains on nodulation, growth, and yield of faba bean was conducted in Wereillu district of Amhara Region, Ethiopia during the rainy season of 2018. The treatments comprised of four levels of faba bean Rhizobium strains (un-inoculated, EAL-1018, EAL-1035 and EAL-17) arranged in a randomized complete block design with three replications. The collected data on yield and yield-related parameters were analyzed using Statistical Analysis System (Statistical Analysis System, version 9.1, SAS Institute Inc, Cary, 2003), version 9.1 and subjected to Duncan’s Multiple Range Test for mean separation when the analysis of variance was significant. Results The result revealed that the effect of EAL-1018 brought significantly (P ≤ 0.05) higher difference on nodule number, nodulation volume, nodule dry weight, biomass yield and grain yield compared to the control. Faba bean strain, EAL-1018 gave 45.6, 27 and 11.6% grain yield advantage over the control, EAL1017 and EAL 1035 respectively. Conclusion Biologically as well as Economically EAL 1018 brought the maximum yield and net benefit (47020.7) compared to the other treatments. Hence, EAL-1018 is recommended for the study area and similar agro—ecologies.